Effect of mitofusin 1 and mitofusin 2 deficiency on electrophysiology parameter following stimulated ischemia reperfusion - Kwek, Xiu Yi (2019)
Background: Acute myocardial infarction (AMI) and the arrhythmias which often follow are among the leading causes of death and disability in Singapore and worldwide. As such novel treatments are required to prevent cardiac arrhythmias following AMI. In an AMI, acute myocardial ischemia and reperfusion can disturb the electrical conduction system of the heart, impact conduction velocity (CV), and result in atrial and ventricular arrhythmias, some of which may be fatal. The gap junction (GJ) protein, connexin 43 (Cx43), is a key determinant of CV, and modulation of Cx43 can affect arrhythmia susceptibility. Changes in mitochondrial shape can impact on mitochondrial function and production of reactive oxygen species (ROS), which may impact Cx43 distribution/phosphorylation, and ultimately affect CV. In this thesis, we investigate the effect of the mitochondrial fusion proteins, Mitofusins 1 and 2 (Mfn 1 and Mfn 2, which are known to modulate mitochondrial shape and function) on Cx43 distribution/phosphorylation and CV in the heart following AMI. Hypothesis: Hearts deficient in Mfn 1 and Mfn 2 will have disturbances in Cx43 distribution and Cx phosphorylation resulting in a reduction in CV, thereby increasing susceptibility to cardiac arrhythmias following AMI. Methodology: We used conditional cardiomyocyte-specific Mfn 1 and Mfn 2 Double Knock Out (MfnDKO) mice (n=3) and wild-type littermate (WT) mice (n=3) to investigate the effect of genetic ablation of Mfn 1 and Mfn 2 on CV (measured by multi-electrode array) at baseline and following stimulated acute ischemia and reperfusion (IR). CV data was analyzed by Clampfit Software. We also performed initial studies investigating the effect of genetic ablation of Mfn 1 and Mfn 2 on Cx43 distribution (measured by immunohistochemistry) and Cx43 phosphorylation (at Ser368 measured by western blotting) in MfnDKO mice (n=1), when compared to WT mice (n=1). Results: CV in heart ventricular tissue from MfnDKO mice was significantly lower (p<0.05) than WT at baseline and following simulated acute IR, a condition which would increase susceptibility to cardiac arrhythmias, suggesting Mfn 1 and Mfn 2 play an important role in the regulation of CV. Our initial data has also suggested that Cx43 localization within cardiomyocytes is altered in MfnDKO mice when compared to WT mice, with partial lateralization of Cx from the GJ to the cytosol, a feature which would affect CV and increase susceptibility to cardiac arrhythmias. Finally, preliminary data has also suggested that phosphorylation of Cx43 at Ser368 is increased in MfnDKO mice when compared to WT mice (n=1 for each group), a feature which would decrease CV and increase susceptibility to cardiac arrhythmias. Conclusions: In summary, in heart ventricular tissue deficient in both Mfn 1 and Mfn 2, CV was reduced, a finding which was associated with partial redistribution of Cx43 away from the GJ, and phosphorylation of Cx43 at Ser368, findings which may be expected to increased susceptibility to cardiac arrhythmias post-AMI. This initial data highlights the Mitofusins as potential therapeutic targets for preventing cardiac arrhythmias post-AMI.